Pemanfaatan Teknologi Penampungan Air Hujan Antisipasi Kekeringan di Desa Pringombo, Kabupaten Gunungkidul - Budiyono, Elizabeth Fiesta Clara Shinta (Jurnal Atma Inovasia, 2023)
Abstract — Pringombo Village is a village located in Rongkop District, Gunung Kidul Regency, Special Region of Yogyakarta. This village has an area of ​​1,431.42 km2 and has a total population of 755,977 people. The distance from this village to the town of Wonosari is 27.3 km. Pringombo Village is located in Rongkop District, Gunung Kidul Regency, Yogyakarta Special Region, Indonesia. The origin of the name Pringombo Village comes from the Javanese ngoko language, namely Pringamba which means Broad Bamboo. This village has a variety of potential ranging from the potential for agricultural products, arts and others. However, apart from its potential, there are findings that most areas in Gunung Kidul are difficult to access water, including Pringombo village. Therefore, the people of Pringombo Village need a solution to be able to help meet their water needs for their daily needs. Keywords : Pringombo Village, Gunungkidul, Village Potential, Rainwater Storage